2014
DOI: 10.1097/mao.0000000000000630
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Idiopathic Sudden Sensorineural Hearing Loss

Abstract: 2B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
4
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 17 publications
1
16
4
1
Order By: Relevance
“…However, it is likely that, as also reported by recent literature [13,14], after a certain age (mostly~65), the success rate drops drastically, with aging having a discontinuous impact on the success. From this study also the time lapse between the onset of the ISSNHL and the IT therapy appears to play a significant role in predicting the therapeutic success, with the PTA values recorded at the first visit significantly influencing the therapeutic success.…”
Section: Discussionmentioning
confidence: 83%
“…However, it is likely that, as also reported by recent literature [13,14], after a certain age (mostly~65), the success rate drops drastically, with aging having a discontinuous impact on the success. From this study also the time lapse between the onset of the ISSNHL and the IT therapy appears to play a significant role in predicting the therapeutic success, with the PTA values recorded at the first visit significantly influencing the therapeutic success.…”
Section: Discussionmentioning
confidence: 83%
“…A report shows that about 50% of patients experience stroke over 2 years after the SHL 23 . However, studies show that SSNHL increases the risk of ischemic stroke in the general population 21 , 24 .…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the long‐term cumulative recurrence rate in the affected ear was 3.5%. In some studies, the recurrence rate has been reported to vary from 0.8% to 4.99%, but none of these studies has described the severity of hearing loss …”
Section: Discussionmentioning
confidence: 99%